An evaluation of UK athletics' clean sport programme in preventing doping in junior elite athletes. Issue 3 (March 2020) - Hurst, Philip; Ring, Christopher; Kavussanu, Maria
Highlights: UK Athletics' Clean Sport programme reduces the risk of unintentional doping. The programme reduces intentional doping in the short term, but not over 3-months. Similar education programmes may need to be strengthened to ensure effects remain. Abstract: The aim of this study was to evaluate UK Athletics' Clean Sport programme in preventing unintentional and intentional doping in junior elite athletes. Track and field athletes (N = 202) attended UK Athletics' Clean Sport programme. This programme delivered information about the World Anti-Doping Agency, drug testing, anti-doping rule violations, use of medications, and risks associated with sport supplements. Participants completed measures related to unintentional (i.e. knowledge of anti-doping rules, intention to use sport supplements, beliefs about sport supplements) and intentional (i.e. doping likelihood, doping moral disengagement) doping at baseline, immediately after the programme, and at 3-month follow-up. Compared to baseline, immediately after the programme, participants had more knowledge about anti-doping rules (mean differences ± SEM = 2.34 ± 0.11; d = 1.40) and lower scores for intention to use supplements (−0.92 ± 0.12; d = 0.44), beliefs about the effectiveness of supplements, (−0.57 ± 0.06; d = 0.45), doping likelihood (−0.16 ± 0.03; d = 0.20), and doping moral disengagement (−0.20 ± 0.04; d = 0.26). At follow-up, knowledge of anti-doping rules (1.94 ± 0.12; d = 1.22), intention to use supplements (−1.26 ± 0.12; d = 0.63), and supplement beliefs (−0.52 ± 0.07; d = 0.42) remained different from baseline, whereas doping likelihood (0.01 ± 0.05; d = 0.01) and moral disengagement (0.13 ± 0.03; d = 0.09) returned to baseline. After attending the programme, participants were less likely to unintentionally dope in the short and medium term and were less likely to intentionally dope in the short term. However, the effects on intentional doping were not maintained after 3-months. These findings suggest that although the programme reduces intentional doping in the short term, it needs to be strengthened to sustain effects in the long term.